A Professional Development Course in Australian Indigenous ESL Teaching - Tan, Kim (The Australian Journal of Indigenous Education, 2000)
The impetus for developing this course came from a consultancy agreement with the Northern Territory Department of Education in 1998 to develop a program to address the special needs of teachers in Aboriginal community schools.